Proceedings of the International Conference and the 10th Congress of the Entomological Society of Indonesia (ICCESI 2019) 2020
DOI: 10.2991/absr.k.200513.032
|View full text |Cite
|
Sign up to set email alerts
|

The Prospect of Nanoinsecticide in Controlling Citrus Aphids Aphis gossypii

Abstract: Nanotechnology is utilized in various fields including agriculture, one of which is in the botanical insecticide formulation. The material used for the formulation of botanical insecticide nano emulsion was tobacco leaf, which was applied to the citrus aphids, Aphis gossypii. This study aimed to determine the effectiveness of botanical insecticide from tobacco leaves in the form of nano emulsion compared to crude extracts. The test was carried out at 4 concentration levels, 0.01%, 0.1%, 1% and 10% and was acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…117–120 For example, Iqbal et al developed a stable neem oil-based nanoemulsion (NE) formulation with bio-inspired adjuvant of Cymbopogon citratus and Prosopis juliflora with long-term storage stability that showed significant insecticidal activity against Bemisia tabaci in eggplant (91.24%) by reducing the surface tension and contact angle. 121 Wuryantini et al compared the efficacy of tobacco plant-derived insecticide nanoemulsion and crude extract and found that the nanoemulsion had better control effect on Citrus aphids than the crude extract, 122 indicating that the use of nanoagents has broad prospects in improving the utilization of active ingredients of plant-derived pesticides.…”
Section: The Main Categories Of Nanobiopesticides and Their Research ...mentioning
confidence: 99%
“…117–120 For example, Iqbal et al developed a stable neem oil-based nanoemulsion (NE) formulation with bio-inspired adjuvant of Cymbopogon citratus and Prosopis juliflora with long-term storage stability that showed significant insecticidal activity against Bemisia tabaci in eggplant (91.24%) by reducing the surface tension and contact angle. 121 Wuryantini et al compared the efficacy of tobacco plant-derived insecticide nanoemulsion and crude extract and found that the nanoemulsion had better control effect on Citrus aphids than the crude extract, 122 indicating that the use of nanoagents has broad prospects in improving the utilization of active ingredients of plant-derived pesticides.…”
Section: The Main Categories Of Nanobiopesticides and Their Research ...mentioning
confidence: 99%
“…140 Wuryantini et al found that the nanoemulsion insecticide derived from tobacco plants exhibited superior control over citrus aphids (Toxoptera aurantii) compared to the crude extract, suggesting that nano-agents offer diverse applications for enhancing the utilization of active ingredients in plant-based pesticides. 141 Integrating polymers into formulations of botanical pesticides to generate nanospheres or nanocapsules can reduce the loss of active ingredients while maintaining controlled release. Encapsulating essential oils at a microscale level can enhance their resistance to oxidation, thermal stability, biological activity, and shelf life, as well as control their volatility and release properties.…”
Section: Nanotechnology Tools For Pest Management In Agriculturementioning
confidence: 99%
“…140 Wuryantini et al found that the nano-emulsion insecticide derived from tobacco plants exhibited superior control over citrus aphids ( Toxoptera aurantii ) compared to the crude extract, suggesting that nano-agents offer diverse applications for enhancing the utilization of active ingredients in plant-based pesticides. 141…”
Section: Why Nano-botanical Insecticides?mentioning
confidence: 99%